Eсonomic aspects of urogenital chlamidiosis treatment - E S Egorova; L B Okonenko (RUDN Journal of Medicine, 2010)
The investigation of urogenital chlamidiosis treatment in the Novgorod region has been conducted. The incidence of urogenital chlamidiosis in the region has been analyzed as well as the assortment of drugs available in the municipal chemist's shops. Sociodemographic picture of a patient with UGC has been designed. The most commonly applied drug protocols have been revealed; of them the most effective and suitable ones have been chosen considering the treatment of side-effects.